2021
DOI: 10.1111/jnu.12706
|View full text |Cite
|
Sign up to set email alerts
|

The experience of the nurse during the COVID‐19 pandemic: A global meta‐synthesis in the year of the nurse

Abstract: Purpose From its beginnings in China in December of 2019, the novel coronavirus COVID‐19 spread and quickly became the center of nursing care and conversation across the globe (WHO, 2020). This meta‐ethnographic study was conducted in order to provide the profession of nursing interpretative explanations of a common experience during the care of patients with COVID‐19. Design and method A literature review focused on the experience of the nurse during the COVID‐19 pandemic revealed a total of 13 qualitative st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
50
0
3

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 56 publications
(57 citation statements)
references
References 19 publications
4
50
0
3
Order By: Relevance
“…Thus, the experience can be both satisfying and demanding. This is also reported by Zipf et al ( 2022 ), in whose study nurses report stress and exhaustion, but also pride in what they have achieved so far.…”
Section: Discussionsupporting
confidence: 80%
See 1 more Smart Citation
“…Thus, the experience can be both satisfying and demanding. This is also reported by Zipf et al ( 2022 ), in whose study nurses report stress and exhaustion, but also pride in what they have achieved so far.…”
Section: Discussionsupporting
confidence: 80%
“…The #PflegeComeBack study concluded that around 120,000–200,000 inactive nurses would consider returning to nursing, depending on circumstances, that is improved working conditions (Paul Hartmann, 2018 ). It has been shown that the pandemic is likely to make conditions even worse (Zipf et al, 2022 ).…”
Section: Introductionmentioning
confidence: 99%
“…Stress, anxiety, and fear were reported in the relevant literature as the most common emotions caused by the COVID-19 pandemic [ 4 , 5 , 6 , 9 , 13 , 44 , 45 ]. The fear of being contaminated was demonstrated specifically by the front-line nurses as they were in close contact with COVID-19 patients.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, lack of information about the novel virus, unpreparedness about the use of personal protection equipment (PPE), and changing policies have increased the levels of stress and uncertainty for all nurses, even for those who did not care for COVID patients [ 4 ]. Nurses globally appeared to share similar feelings of fear, moral conflict, need for preparedness and safety, sense of duty, and exhaustion [ 5 ]. Issues of vulnerability, family protection from possible infection, and yet professional commitment and collegiality appeared to be issues of significant importance for nurses all over the world [ 6 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation